Investigation of residual hepatitis C virus in presumed recovered subjects - Fujiwara, Kei (2013)
Recent studies have found hepatitis C virus (HCV) RNA in peripheral blood mononuclear cells (PBMCs) of the majority of presumed recovered subjects. We investigated this unexpected finding using samples from patients whose HCV RNA and anti-HCV status had been serially confirmed. HCV RNA was detected in PBMCs from 66/67 chronic HCV carriers. Subpopulation analysis revealed that the viral load (log copies/10(6) cells) in B cells (4.14 ± 0.71) was higher than in total PBMCs (3.62 ± 0.71, p<0.05), T cells (1.67 ± 0.88, p<0.05), and non-B/T cells (2.48 ± 1.15, p<0.05). HCV negative-strand RNA was not detected in PBMCs from any of 25 chronically infected patients. No residual viral RNA was detected in total PBMCs or plasma of 59 presumed recovered subjects (11 spontaneous, 48 treatment-induced) using nested real-time PCR with a detection limit of 2 copies/µg RNA (from ∼1x10(6) cells). PBMCs from two healthy HCV-negative blood donors became HCV RNA positive, with B-cell predominance, when mixed in vitro with HCV RNA positive plasma, thus passively mimicking cells from chronic HCV carriers. No residual HCV was detected in liver or other tissues from two spontaneously recovered chimpanzees. Conclusion: 1) HCV RNA was detected in PBMCs of most chronic HCV carriers and was predominant in the B cell subpopulation; 2) HCV detected in PBMCs was in a non-replicative form; 3) HCV passively adsorbed to PBMCs of healthy controls in vitro becoming indistinguishable from PBMCs of chronic HCV carriers; 4) Residual HCV was not detected in the plasma or PBMCs of any spontaneous or treatment recovered subjects or in chimpanzee liver suggesting that the classic pattern of recovery from HCV infection is generally equivalent to viral eradication.